MORPHOMETRIC CHARACTERISTICS, PROPORTITION, TOTAL FENOL CONTENT AND PROFIL PHENOLICS OF AVOCADO (Persea americana, Mill) PULP, SEED AND PEEL VARIETY OF IJO PANJANG AND IJO BUNDAR - Wuri Marsigit (Jurnal Agroindustri, 2016)
The aims of the study were to compare morphometrics chararcteristic, porportion, total phenolics and profil phenoilic of pulp, seed and peel of avocado (Persea americana, Mill) variety of ijo panjang and ijo bundar. Morphometrics characteristics were measured by using ruler and calipers. Fruit proportions were determined by using digital balance, Total phenolics was analized by Folin-Ciocalteu methods and profil phenolics were analized by using HPLC. The result of the studies found that variety of ijo panjang had longer size, smaller seed diameter and thicker peel than ijo bundar. Seed proportion variety ijo panjang was lower than ijo bundar, but pulp and peel were higher. Total phenolics content of ijo panjang lower in pulp and seed, but higher in peel. Profil phenolics compound in avocado consist of cathechin, hydroxybenzoic acid, flavonol and procyanidin and hydroxycinnamic acid. Phenolics compounds in pulp were higher in ijo panjang variety, except hydroxycinnamic acid. Phenolics compounds in seed was higher in variety of ijo bundar. Phenolics Compounds in peel were hinger in ijo panjang, except hydroxybenzoic acid.